The Effect Of Family Psychoeducation Therapy On Family Ability In Caring For Patients With Schizophrenia In The Work Area Of Kumun Public Health Center - Ulia, Azma; Suzana, Moza; Lunajua Putri , Reginayla (Jurnal Keperawatan Universitas Jambi, 2025)
Abstract Based on background as much as 6,7 per 1000 households have households members (ART) who suffer from mental disorders. This shows that the family’s ability to care for people with mental disorders is very important to prevent relapse in schizophrenia patients.The aim of this research is to determine the average family capacity before and after it was carried out family psychoeducation therapy and also to find out whether there is an influence of family psychoeudcation therapy on the ability of families to care for schizophrenic patients in the Kumun health center workingarea. Family Psychoeducation Therapy is an action or therapy given to families in the form of actions that combine education, coping methods andthe family’s ability to solve problems, stress and burdens that arise when caring for family members who suffer from schizophrenia.This type of research is a Quasy Ekperiment with a One Group Pretest and Posttest approach with a sample size of 16 respondents. Based on the research results obtained, research results wereobtained before family psychoeducation therapy was carried out with an average value of 6,31 and after family psychoeducation therapy was carried out with an average value of 8,88 with a p-value of <0,005 which shows that there is an influence offamily psychoeducation therapy on ability. Family in caring for schizophrenic patients. The implementation of family psychoeducation therapy apart from being able to improve the family’s abilities, this therapy can also help the healing process of schizophrenia patients. The conclusion is that there is a difference in the average ability of families to care for patients before therapy is given and after family psychoeducation therapy is given.It is hopedthat this research will prodive insight and understanding and can also become a source of reference for further research and this family psychoeducation therapy can be applied ti anticipa the problem of family stress, burdens that can arise when caring for schizophrenia patients.